High photocatalytic performance of 3D porous-structured TiO2@natural rubber hybrid sheet on the removal of indigo carmine dye in water - Sriwong, Chaval; Choojun, Kittisak; Sriwong, Sukanpirom (My University, 2019)
Due to the high efficiency of photocatalytic process for the environmental treatments, titanium dioxide (TiO2) is a popular used as photocatalyst material. However, the practical uses of TiO2 in powder form have some drawbacks as well as the difficult reusability. In this work, 3D porous-structured TiO2@natural rubber (TNR) hybrid sheets with high photocatalytic performance were presented. TNR hybrid sheets prepared by a facile and low-cost method, which is based on the mixing of natural rubber (NR) latex (60% high ammonia) and ammoniacal TiO2 (P25) suspension, followed by vacuum filtration through a sintered glass template to make a 3D porous network structure on the surface of the sheets. The obtained TNR sheet samples were characterized by scanning electron microscopy (SEM), energy dispersive X-ray spectrometer (EDX), X-ray diffractometer (XRD) and reflection Fourier transformed infrared spectroscopy (FT-IR) techniques. The results showed that the surface morphologies of TNR hybrid sheets appeared as porous-structured which had high roughness and with various tiny pores on the surface. The photocatalytic properties of the prepared TNR hybrid sheets were tested using indigo carmine (IC) dye under UV light irradiation. It was found that the highest photodegradation efficiency was achieved with the TNR_5 wt% hybrid sheet sample. Compared with the sheets reported in previous works, the TNR sheet shows higher efficiencies than those sheets due to its higher amount of TiO2 particles at the surface, more porous structure with high rough surface, and abundance of tiny pores on the TNR sheet surface. Moreover, the recyclability and stability of TNR sheet indicated that upon using 10 cycles (remains 98% efficiency), in which the stability of the sheet surface well-confirmed by SEM and XRD techniques, as well. From above the study, this 3D porous-structured TNR hybrid sheet could be a new alternative strategy for the water or wastewater treatment in industry concerning with the easy use, recovery, reusability and stability of the photocatalysts.
Keywords: 3D structure; Indigo carmine (IC); Photocatalytic process; TiO2-rubber sheet; Titanium dioxide (TiO2)